Cyclooxygenase-2 expression in hepatocytes attenuates non-alcoholic steatohepatitis and liver fibrosis in mice - Motiño, Omar (2016)
Cyclooxygenase-2 (COX-2) is involved in different liver diseases but little is known about the significance of COX-2 in the development and progression of non-alcoholic steatohepatitis (NASH). This study was designed to elucidate the role of COX-2 expression in hepatocytes in the pathogenesis of steatohepatitis and hepatic fibrosis. In the present work, hepatocyte-specific COX-2 transgenic mice (hCOX-2-Tg) and their wild-type (Wt) littermates were either fed methionine-and-choline deficient (MCD) diet to establish an experimental non-alcoholic steatohepatitis (NASH) model or injected with carbon tetrachloride (CCl4) to induce liver fibrosis. In our animal model, hCOX-2-Tg mice fed MCD diet showed lower grades of steatosis, ballooning and inflammation than Wt mice, in part by reduced recruitment and infiltration of hepatic macrophages, with a corresponding decrease in serum levels of pro-inflammatory cytokines. Furthermore, hCOX-2-Tg mice showed a significant attenuation of the MCD diet-induced increase in oxidative stress and hepatic apoptosis observed in Wt mice. Even more, hCOX-2-Tg mice treated with CCl4 had significantly lower stages of fibrosis and less hepatic content of collagen, hydroxyproline and pro-fibrogenic markers than Wt controls. Collectively, our data indicates that constitutive hepatocyte COX-2 expression ameliorates NASH and liver fibrosis development in mice by reducing inflammation, oxidative stress and apoptosis and by modulating activation of hepatic stellate cells, respectively, suggesting a possible protective role for COX-2 induction in NASH/NAFLD progression.